Inhibition and eradication activity of truncated α-defensin analogs against multidrug resistant uropathogenic Escherichia coli biofilm - Moazzezy, Neda; Asadi Karam, Mohammad Reza; Rafati, Sima; Bouzari, Saeid; Oloomi, Mana (PLOS ONE, 2020)
Today the development of antibiotic resistance, especially in the treatment of bacterial infections associated with biofilms, has led to increasing the importance of antimicrobial peptides (AMPs). In this work, antimicrobial and synergistic activity of three truncated HNP-1 analogs (2Abz14S29, 2Abz23S29, and HNP1ΔC18A) with β-lactam (amoxicillin and cefixime) and fluoroquinolones (ciprofloxacin and norfloxacin) antibiotics against multidrug-resistant (MDR) uropathogenic E. coli clinical isolates were evaluated. The anti-biofilm potential of peptides at different stages was also investigated. All peptides exhibited additive activity just with β-lactam antibiotics in a checkerboard synergy assay. Inhibition and eradication of MDR uropathogenic E. coli biofilm were shown by all test peptides at different concentrations. Thus, truncated HNP-1 analogs (2Abz14S29, 2Abz23S29, and HNP1ΔC18A) may have the potential for the treatment of urinary tract infections (UTIs) caused by biofilm-forming MDR uropathogenic E. coli.